2018
DOI: 10.1007/s12594-018-1073-9
|View full text |Cite
|
Sign up to set email alerts
|

Signatures of Holocene Hydrological Processes from Sedimentary Archives in Southwestern India: Case Studies from Wetlands of Kerala Coast

Abstract: The subsurface sediments of the Kerala coast provided signatures of hydrological processes that have influenced in the modifications and conversion of larger part of the lowland and the forest cover into a major wetland system during the Holocene which in turn has transformed into one of the best carbon sinks in the Indian subcontinent. The most significant and well recognized signature is the paleoflood event during the Early to Middle Holocene coinciding with the Holocene Climate Optimum (HCO). The excessive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…One of the most efficient tools for unravelling the palaeoclimatic conditions that prevailed during the depositional processes is geochemical studies of silicate and non-silicate mineral phases in sediments (Clift et al, 2002;Li et al, 2004;Mishra et al, 2019;Yang et al, 2003Yang et al, , 2004Yang et al, , 2007. Although several geochemical tools have been widely used in many parts of the world, not enough studies have been reported from the Indian subcontinent to decode the past climatic conditions in the sedimentary archives (Mishra et al, 2019;Sarin et al, 1979;Das and Krishnaswami, 2007;Pattan et al, 2008;Veena et al, 2013;Tripathy et al, 2014;Kumaran et al, 2018). Here an attempt has been made to address a few aspects of sediment geochemistry of borehole cores retrieved from the northern part of Kerala of Peninsular India to decode partially the palaeoclimatic records.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most efficient tools for unravelling the palaeoclimatic conditions that prevailed during the depositional processes is geochemical studies of silicate and non-silicate mineral phases in sediments (Clift et al, 2002;Li et al, 2004;Mishra et al, 2019;Yang et al, 2003Yang et al, , 2004Yang et al, , 2007. Although several geochemical tools have been widely used in many parts of the world, not enough studies have been reported from the Indian subcontinent to decode the past climatic conditions in the sedimentary archives (Mishra et al, 2019;Sarin et al, 1979;Das and Krishnaswami, 2007;Pattan et al, 2008;Veena et al, 2013;Tripathy et al, 2014;Kumaran et al, 2018). Here an attempt has been made to address a few aspects of sediment geochemistry of borehole cores retrieved from the northern part of Kerala of Peninsular India to decode partially the palaeoclimatic records.…”
Section: Introductionmentioning
confidence: 99%